2018
DOI: 10.1002/aic.16103
|View full text |Cite
|
Sign up to set email alerts
|

Metal nanoparticles in ionic liquid‐cosolvent biphasic systems as active catalysts for acetylene hydrochlorination

Abstract: Ionic liquid (IL)‐stabilized metal nanoparticles (NPs) have attracted increased attention as novel catalysts for various reactions due to their excellent stability and high activity. However, the high viscosity of ILs limits their applications. Here, for the first time, we reported an NPs@IL‐cosolvent liquid–liquid biphasic system for metal NPs catalysis. The NPs were successfully confined to IL phase, and abundant IL droplets containing NPs were generated under the reactant flow. The NPs@IL droplets served as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 61 publications
(85 reference statements)
0
23
0
Order By: Relevance
“…half of the initial catalytic activity of state-of-the-art Au SACs, which is more than three times higher compared to the activity levels reported in literature for platinum-based catalysts, which were likely composed of Pt nanoparticles. 27 , 34 , 36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…half of the initial catalytic activity of state-of-the-art Au SACs, which is more than three times higher compared to the activity levels reported in literature for platinum-based catalysts, which were likely composed of Pt nanoparticles. 27 , 34 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…half of the initial catalytic activity of state-of-the-art Au SACs, which is more than three times higher compared to the activity levels reported in literature for platinum-based catalysts, which were likely composed of Pt nanoparticles. 27,34,36 Mechanistic studies. To gain atomistic insight into the structure-performance relationships of distinct Pt sites in acetylene hydrochlorination, DFT was employed.…”
Section: Activity Descriptors For Platinum Catalysts Acetylene Hydromentioning
confidence: 99%
See 1 more Smart Citation
“…26−28 The LCC-ILs were prepared via anion exchange of the corresponding phosphonium bromide to phosphonium hydroxide and subsequent neutralization with long-chain fatty acids. 26,29 The LCC-ILs prepared in this work were all transparent amber liquids at room temperature, and the related viscosity was evaluated from 450 to 600 cP at 298 K (Figure S1). The glass transition temperatures or melting points of the ILs with n-octyltributylphosphonium ([P 4448 ] + ) cations were relatively low (between −80 and −40 °C), while those of the n-dodecyltribultylphophonium ([P 444 (12) ] + )-based ILs were approximately −18 °C (Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Actually, the leaching of the PdCl 2 active component was oen thought to be the cause of deactivation for Pd-based catalysts in the hydrochlorination of acetylene. [44][45][46]51,52 For example, Wang 41 demonstrated that 44.7% Pd species had leached from HY zeolite-supported Pd-based catalysts aer reaction; in addition, Wang suggested that the Pd loss was responsible for the deactivation of the Pd/HY catalysts, and the ICP analysis indicated that about 37.8% Pd species had been lost aer 10 h time on stream as compared to the case of the fresh catalyst. Fig.…”
Section: Catalytic Characterizationmentioning
confidence: 99%